Prevalence of anemia in exclusively breastfed full term babies between 3-6 months of age - Marol, Rajakumar; Marol, Renuka (International Journal of Contemporary Pediatrics, 2021)
Background: WHO recommends exclusive breast feeding for 6 months without examination for anemia. However there are concerns about the feasibility and safety of this recommendation. Cochrane review studies especially in developing countries, suggest that exclusive breastfeeding up to 6 months without iron supplementation may compromise the hematologic status of children leading to IDA and its consequences. So the question arises; does absolute breast feeding protect infants from anemia during first 6 months of life? The present study was conducted to estimate the prevalence of anemia in exclusively breastfed babies between 3-6 months of age. Methods: This was a retrospective study conducted between January 2019 and December 2019 at Shivajyoti Institute of Child Health-Haveri, in exclusively breastfed infants aged between 3-6 months who attended OPD and underwent complete blood count examination. Hemoglobin levels were collected and anemia was defined and classified as per WHO criteria for 6-24 months old children. Results: Out of 81 infants 52 were males and 29 were females. Age wise, 26 babies were 3 months, 34 were 4 months and 21 were 5 months old. A total of 71 children had anemia; 49 mild, 20 moderate and 2 severe. The prevalence of anemia was 87.6% and it was highest (92.3%) at 3 months of age. Conclusions: Exclusively breastfed infants between 3-6 months are at increased risk of anemia. Therefore infants after 3 months, should be evaluated for anemia and iron deficiency which is the commonest cause of anemia. Such infants should be supplemented with oral iron in addition to exclusive breast feeding for 6 months, to prevent adverse effects of IDA on infants’ growth and development.